Diastereoselective anodic hetero- and homo-coupling of menthol-, 8-methylmenthol- and 8-phenylmenthol-2-alkylmalonates - Letzel, Matthias C.; Schäfer, Hans J.; Fröhlich, Roland (Beilstein Journal of Organic Chemistry, 2017)
Diastereoselective radical coupling was achieved with chiral auxiliaries. The radicals were generated by anodic decarboxylation of five malonic acid derivatives. These were prepared from benzyl malonates and four menthol auxiliaries. Coelectrolyses with 3,3-dimethylbutanoic acid in methanol at platinum electrodes in an undivided cell afforded hetero-coupling products in 22–69% yield with a diastereoselectivity ranging from 5 to 65% de. Electrolyses without a coacid led to diastereomeric homo-coupling products in 21–50% yield with ratios of diastereomers being 1.17:2.00:0.81 to 7.03:2.00. The stereochemistry of the new stereogenic centers was confirmed by X-ray structure analysis and 13C NMR data.
Keywords: anodic decarboxylation; diastereoselectivity; Kolbe electrolysis; radical hetero-coupling; radical homo-coupling

(untitled) - Porter, N. A.; Giese, B.; Curran, D. P. (Acc. Chem. Res., 1991)

(untitled) - Smadja, W. (Synlett, 1994)

Stereochemistry of Radical Reactions - Curran, D. P.; Porter, N. A.; Giese, B. (VCH, 1996)

(untitled) - Sibi, M. P.; Porter, N. A. (Acc. Chem. Res., 1999)

(untitled) - Sibi, M. P.; Manyem, S.; Zimmerman, J. (Chem. Rev., 2003)

(untitled) - Srikanth, G. S. C.; Castle, S. L. (Tetrahedron, 2005)

Comprehensive Organic Synthesis - Subramanian, H.; Landais, Y.; Sibi, M. P. (Radical Addition Reactions, 2014)

Encyclopedia of Radicals in Chemistry, Biology and Materials - Yang, Y.-H.; Sibi, M. P. (Stereoselective Radical Reactions, 2012)

Comprehensive Chirality - Guindon, Y.; Godin, F.; Mochirian, P. A.; Prevost, M. (Selected diastereoselective reactions: free radical additions and cyclizations, 2012)

(untitled) - Eichin, K.-H.; Beckhaus, H.-D.; Hellmann, S.; Fritz, H.; Peters, E.-M.; Peters, K.; von Schnering, H.-G.; Rüchardt, C. (Chem. Ber., 1983)

(untitled) - Peyman, A.; Beckhaus, H.-D.; Kramer, D.; Peters, K.; von Schnering, H.-G.; Rüchardt, C. (Chem. Ber., 1991)

(untitled) - Wessig, P.; Wettstein, P.; Giese, B.; Neuburger, M.; Zehnder, M. (Helv. Chim. Acta, 1994)

(untitled) - Wessig, P.; Lindemann, U.; Neuburger, M.; Zehnder, M. (J. Inf. Rec., 1996)

(untitled) - Lomölder, R.; Schäfer, H. J. (Angew. Chem., 1987)
Angew. Chem., Int. Ed. Engl. 1987, 26, 1253–1254. doi:10.1002/anie.198712531

(untitled) - Klotz-Berendes, B.; Schäfer, H. J.; Grehl, M.; Fröhlich, R. (Angew. Chem., 1995)
Angew. Chem., Int. Ed. Engl. 1995, 34, 189–191. doi:10.1002/anie.199501891

Electroorganic Chemistry - Schäfer, H. J. (CRC Press, 2016)

(untitled) - Reiffers, S.; Wynberg, H.; Strating, J. (Tetrahedron Lett., 1971)

(untitled) - Krapcho, A. P.; Jahngen, E. G. E., Jr; Kashdan, D. S. (Tetrahedron Lett., 1974)

(untitled) - Buschmann, H.; Scharf, H. D. (Synthesis, 1988)

(untitled) - Červinka, O.; Svatoš, A.; Masojídková, M. (Collect. Czech. Chem. Commun., 1990)

(untitled) - Schäfer, H. J. (Top. Curr. Chem., 1990)

(untitled) - Johnes, G. B.; Chapman, B. J. (Synthesis, 1995)

(untitled) - Effenberger, F.; Kottmann, K. (Tetrahedron, 1985)

(untitled) - Dickinson, T.; Wynne-Jones, W. F. K. (Trans. Faraday Soc., 1962)

(untitled) - Kipphardt, H.; Enders, D. (Kontakte (Darmstadt), 1985)

(untitled) - Bednarski, M.; Danishefsky, S. (J. Am. Chem. Soc., 1986)

(untitled) - Whitesell, J. K.; Bhattacharya, A.; Buchanan, C. M.; Chen, H. H.; Deyo, D.; James, D.; Liu, C.-L.; Minton, M. A. (Tetrahedron, 1986)

(untitled) - Oppolzer, W.; Löhner, H. J. (Helv. Chim. Acta, 1981)

(untitled) - Comins, D. L.; Guerra-Weltzien, L. (Tetrahedron Lett., 1996)

(untitled) - Siering, C.; Grimme, S.; Waldvogel, S. R. (Chem. – Eur. J., 2005)

(untitled) - Ihara, M.; Takahashi, M.; Taniguchi, N.; Yagui, K.; Niitsuma, H.; Fukumoto, K. (J. Chem. Soc., Perkin Trans. 1, 1991)

(untitled) - Zhang, A.; Mohan, R. M.; Cook, L.; Kazanis, S.; Peisach, D.; Foxman, B. M.; Snider, B. B. (J. Org. Chem., 1993)

Studien zur diastereoselektiven Kupplung anodisch erzeugter Radikale - Klotz-Berendes, B. (Universität Münster, 1994)

Studien zur diastereoselektiven Kupplung anodisch erzeugter Radikale in Hetero- und Homokupplungen - Letzel, M. (Universität Münster, 1997)

(untitled) - Porter, N. A.; Su, Q.; Harp, J. J.; Rosenstein, I. J.; McPhail, A. T. (Tetrahedron Lett., 1993)

(untitled) - Langer, T.; Illich, M.; Helmchen, G. (Synlett, 1996)

(untitled) - Langer, T.; Illich, M.; Helmchen, G. (Tetrahedron Lett., 1995)

(untitled) - Evans, D. A.; Takacs, J. M. (Tetrahedron Lett., 1980)

(untitled) - Evans, D. A.; Ennis, M. D.; Mathre, D. J. (J. Am. Chem. Soc., 1982)

(untitled) - Eberson, L. (Electrochim. Acta, 1967)

(untitled) - Eberson, L.; Gränse, S.; Olofsson, B. (Acta Chem. Scand., 1968)

(untitled) - Eberson, L. (Acta Chem. Scand., 1963)

(untitled) - Eberson, L.; Ryde-Petterson, G. (Acta Chem. Scand., 1973)

(untitled) - Eberson, L.; Nyberg, K.; Servin, R. (Acta Chem. Scand., Ser. B, 1976)

(untitled) - Hawkes, G. E.; Utley, J. H. P.; Yates, G. B. (J. Chem. Soc., Perkin Trans. 2, 1976)

(untitled) - Utley, J. H. P.; Yates, G. B. (J. Chem. Soc., Perkin Trans. 2, 1978)

(untitled) - Solladié-Cavallo, A.; Csaky, A. G.; Gantz, I.; Suffert, J. (J. Org. Chem., 1994)